Appraising the role of building contracting firms in the digitalisation of artisans’ skills development to achieving Sustainable Development Goal 8 - Ebekozien, Andrew; Hafez, Mohamed; Aigbavboa, Clinton; Shariff, Mohamad Shakri Mohmad; Nwaole, Angeline Ngozika Chibuike; Samsurijan, Mohamad Shaharudin; Ghazali, Nooramira; Aigbe, Romeo Osayande; Ebekozien, Ehimemen Osebuohien (Frontiers in Built Environment, 2025)
IntroductionStudies reveal that firms’ leadership acumen, global best human resources practices, sustainable business, and organisational excellence through digitalisation can boost employees’ skills development and economic growth. Extant studies reveal a scarcity of empirical materials regarding building contracting firms’ role in developing artisans’ skills, particularly in improving the achievement of Sustainable Development Goal (SDG) 8 (Decent Work and Economic Growth). This study appraises the role of building contracting firms in the digitalisation of Nigerian artisans’ skills development and recommends ways to promote them and, by extension, improve the achievement of SDG 8.MethodsThis research utilised a qualitative method and interviewed 36 participants from Lagos and Abuja to achieve saturation at the 31st participant. It also adopted a thematic approach to analyse the data manually. Results and discussionFindings show that the contracting firm’s role in digitalising artisans’ skills development is pertinent, but implementation may face some barriers. The perceived barriers were clustered into three groups. Findings reveal that accomplishing SDG 8 may be threatened if these barriers are not curbed, and recommend ways to promote the firm in digitalising artisans’ skills development to accomplish SDG 8. This study would stir stakeholders to embrace digitalisation to improve decent work, youth employment, and economic growth.